‘Malaysia My Second Home’ (MM2H): Retirees’ motivations, satisfaction, and post-satisfaction intentions / Wong Kee Mun - Wong, Kee Mun (2015)
‘Malaysia My Second Home’ is an international retirement migration (IRM) programme aimed at attracting the lucrative retiree market to choose Malaysia as their residence. Despite the widely researched IRM studies in the Western context, limited knowledge is available on the participants’ motivation, satisfaction, and post-satisfaction intentions (i.e. exit, voice, loyalty, neglect). Relationships among variables have also not been empirically established. Using the Interdependence theory as theoretical underpinning, the study combines the push-pull motivation theory, perceived performance theory, transnationalism, and exit, voice, loyalty and neglect theory. The conceptualised model - Second Home Retirement (SHR) – is developed through a two-phase sequential mixed-method: qualitative through individual in-depth interviews and quantitative with questionnaire data collection. Four stages of new scale development as proposed by Ashill and Jobber (2010), Churchill (1979), DeVellis (2003), Hinkin (1995), Malhotra (2007) and Nunnally and Bernstein (1994) were performed. The research findings provide theoretical contribution which simultaneously extend the IRM and second home tourism knowledge, and propose the application of the SHR model in extending the interpretation of the existing retirement migration framework introduced by Haas and Serow (1993). The scale development for several constructs concurrently (i.e. push and pull motivations, transnational behaviours), and the use of data triangulation are the key methodological contributions of the study. Several analytical techniques adopted, including descriptive analysis, reliability test, EFA, CFA and SEM. The qualitative findings reveal several new indicators for both push and pull motivations, which then went through a stringent new scale development process. The second stage of quantitative approach uncovers two most important push motivation dimensions which influence the retirees’ overall satisfaction: ‘Unfavourable political and security’ and `Escapism’. The most important pull motivation dimensions are ‘amenities and facilities’, ‘socialisation’, and ‘people and communication’. Both push and pull motivations positively influence the retirees’ overall satisfaction. However, the destination attributes are vulnerable with the inclusion of transnational activities, performed by the international retirees in Malaysia. When the retirees are satisfied, they are likely to be loyal to the retirement destination, and unlikely to provide much feedback to the practitioners. On the contrary, when they are dissatisfied, they are likely to leave the retirement destination, by exiting the retirement program or simply act ignorantly and spend less time in the retirement destination. Second home retirement destination managers may utilise the attributes of motivations, retirees transnational behaviours, and their challenges experienced to better understand the retirees’ needs and requirements. In all, the agility of second home tourism policy makers and destination marketers to manage the conditions of the surrounding environment and to satisfy the retirees’ requirements is essential to ensure the attractiveness and success of its second home retirement programme.